(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
A second autopsy is a repeat examination of an autopsied body by another forensic expert or a panel of doctors, done on the orders of government officials or a court. A second autopsy is usually done whenever there is suspicious foul play, particularly in cases like homicides, custodial deaths, death overseas, etc. But recently, it has been done more often at the request of the deceased relatives when they are not convinced by the first autopsy. Here we discuss a case of a 39 years old male with a history of seizures in police custody. He was treated and sent back to police custody. After 2-3 days of discharge, he developed seizures again and was taken to a hospital, declared brought dead. The relatives were unsatisfied with the first autopsy and demanded a second autopsy which was performed 21 days after the first autopsy.